Promoting Preschoolers' Mental-Emotional Conceptualization and Social Understanding: A Shared Book-Reading Study. Issue 4 (19th May 2021) - Bergman Deitcher, Deborah; Aram, Dorit; Khalaily-Shahadi, Mabsam; Dwairy, Mona
ABSTRACT: Research Findings: The current study explored the impact of a brief, small-group, shared book-reading (SBR) intervention on preschoolers' expression of thoughts and emotions and their social understanding. To structure discourse around the book, we adapted Ellis's ABC model, which focuses on understanding activating events (A), related beliefs (B), and emotional consequences (C). Participants included 116 Arab-Israeli children ( M = 75 months, SD = 0.28), who were randomly divided into intervention and comparison groups. Over five SBR meetings, small groups of children in the intervention group were exposed to a book's text rich in mental and emotion terms and discussion of the characters' thoughts, emotions, behaviors, and situations and consequences. The comparison group text and discussions focused on the book's plot, characters, and actions. We found that the intervention group significantly improved in their expression of emotion terms, and their ability to connect thoughts to emotions, define social problems, and generate solutions. Practice & Policy : The ABC model provides a readily available language with which to connect book characters' thoughts and emotions, focus on social situations and consequences, and connect these elements to children's lives. This intervention can promote preschoolers' socio-emotional understanding within the typical group context of SBR in preschools.